DISCURSIVE STRATEGIES FOR HANDLING THE SPREAD OF ONLINE GAMBLING AMONG THE YOUNG GENERATION WITH POSITIVE DISCOURSE ANALYSIS IN ONLINE ARTICLES - Sumiati Sumiati; Jufri Jufri (LLDIKTI Wilayah X, 2025)
Gambling is increasingly spreading and becoming a big problem in society and has a very bad impact on the people who participate in or are involved in gambling. Moreover, these activities have penetrated to children or the younger generation and have become a source of anxiety and anxiety in the community. Various studies have found a variety of expressions that show expressions of anxiety and anxiety in society. Using the Positive Discourse Analysis (PDA) framework, it not only explores social problems, but also seeks solutions by identifying ways in which language can be used to drive change. The purpose of this research focuses on discursive strategies used by observers who are also policy makers of the Indonesian government. A total of 3 attriches were analyzed through the stages of identification, interpretation, and explanation of the data found in the article with the theme of online gambling among the younger generation which includes framing online gambling as a serious concern because of its negative impact on various aspects of society's social, economic, and psychological life. The overall discursive strategy is used to build solidarity, arouse optimism and collective aski as a moral strength in facing online gambling. This study shows that PDA can be an analytical tool to examine online gambling discourse as a form of crisis discourse.